The Effect of Risk Management Implementation on Operational Efficiency in Event Organizers: An Empirical Intervention-Based Study at CV RAP PADUKARYA - Desmon Gunadi Siagian; Katrin Jenny Sirait; Jamardua Haro; Rismawati Situmorang (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The event organizer industry operates in a dynamic environment characterized by high uncertainty, tight schedules, and complex coordination, making operational efficiency highly dependent on effective risk management practices. However, many small and medium-sized event organizers still rely on reactive approaches that often lead to inefficiencies in time, cost, and operational readiness. This study aims to examine the effect of risk management implementation on operational efficiency in event organizer activities. Operational efficiency is conceptualized as a multidimensional construct consisting of schedule efficiency, cost efficiency, and operational preparedness. This study employs a quantitative evaluative approach using a quasi-experimental one-group pre–post design. Due to the absence of primary field data, a simulation-based quantitative method is applied to represent realistic operational conditions. Data analysis is conducted using descriptive statistics, paired sample t-tests, effect size analysis, and reliability testing. The results indicate statistically significant improvements across all dimensions of operational efficiency following the implementation of risk management practices. Among these dimensions, operational preparedness shows the strongest improvement. The findings suggest that risk management functions as an organizational capability that enhances readiness and adaptability in project-based service environments. This study concludes that simple and feasible risk management practices can substantially improve operational efficiency in event organizer organizations.